MANAGEMENT CONTROL AND ITS FUNCTIONS IN ORGANIZATIONS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article provides information about managerial activities, management and its functions in organizations. Analytical comments are made.